Dark shadows - Zanuck, Richard D.; Curtis, Dan, 1927-2006.; Grahame-Smith, Seth.; August, John.; Burton, Tim, 1958-; Depp, Johnny; Pfeiffer, Michelle, 1957-; Bonham Carter, Helena, 1966-; Green, Eva, 1980-; Warner Home Video (Firm); Warner Bros. Pictures (1969- ); Village Roadshow Pictures; et al. (Burbank, CA : Warner Home Video, 2012)
Imprisoned vampire Barnabas Collins is inadvertently freed from his tomb and emerges into the very changed world of 1972. He returns to Collinwood Manor to find that his once-grand estate has fallen into ruin. The dysfunctional remnants of the Collins family have fared little better and are in need of his protection.
DVD, region 1, widescreen (16x9) presentation; Dolby Digital 5.1 surround.
English, Spanish or French dialogue; Spanish or French subtitles.
English subtitles for the deaf and hard-of-hearing.
Title from container.
Featuring Johnny Depp, Michelle Pfeiffer, Helena Bonham Carter, Eva Green, Jackie Earle Haley, Jonny Lee Miller, Chloë Grace Moretz, Bella Heathcote.
Director of photography, Bruno Delbonnel ; film editor, Chris Lebenzon ; music by Danny Elfman.
Keywords: Vampires -- Drama; Witches -- Drama; Supernatural -- Drama; Feature films; Vampire films; Comedy films; Fiction films; Video recordings for the hearing impaired